Patient reported factors influencing the decision‐making process of men with localised prostate cancer when considering Active Surveillance—A systematic review and thematic synthesis. Issue 3 (4th October 2021) - Cunningham, Maggie; Murphy, Mike; Sweeney, Paul; Richards, Helen L.
Abstract: Objectives: Outcomes for men with localised prostate cancer managed with Active Surveillance (AS) are similar to outcomes for men who have received Active Treatment. This review explore men's perceptions of the factors that influence their decision‐making process when considering AS. Method: A systematic review of studies was conducted up to May 2021, including qualitative studies which explored the decision making of men with localised prostate cancer when considering AS. Evidence was analysed using thematic synthesis. Results: Thirteen papers, including 426 men, met inclusion criteria and were analysed in the review. Approximately half of the men had chosen AS and half had chosen Active Treatment. The choice of AS was not a one‐off decision but rather an ongoing behaviour. Four themes were identified and considered within a temporal model: pre‐diagnosis representations of cancer and treatment; experience of testing and diagnosis; patient decision making; and emotional adjustment to AS. Key barriers and facilitators to men choosing AS were identified. In deciding whether or not to choose AS, men balanced a desire for quality of life against fear of cancer progression. Conclusions: Both cognitive representations and emotional arousal influence how men decided whether or not to opt for AS. Interventions tailored to elicit and address emotional appraisals of risk, and increase trust in AS protocols, may be of value in helping men to make decisions around treatment for localised prostate cancer.